PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP PROFITABILITAS (STUDI KASUS PADA PT TIMAH TBK PERIODE 2019-2022) - Cahyaningrum, Arfenita -; Firnanda, Ninda Maya; Zahroh, Maidatus -; R Pandin, Maria Yovita (Jurnal Ekonomi : Journal of Economic, 2024)
The influence of green accounting on the profitability of mining sector businesses listed on the Indonesia Stock Exchange (IDX) is examined in this article. Green accounting, as determined by the environmental expenses that the businesses disclose, is the independent variable under investigation. The profitability indicators of net profit margin (NPM), return on equity (ROE), and return on asset (ROA) are the dependent variables. PT. Timah Tbk makes up the study population, and the sample period runs from 2019 to 2022 for four years. Using the statistical program SPSS, a straightforward linear regression analysis is the analytical technique used. F-tests and t-tests are used to test hypotheses, with a significance threshold of 5%. The analysis's findings suggest that, at least in part, green accounting has no statistically significant effect on the profitability levels as determined by NPM, ROA, and ROE.